Are new devices required to reduce contrast load in the cath lab, or is behavioral change sufficient?. Issue 6 (17th November 2017) - Rogers, Toby; Satler, Lowell F.
Key Points: A novel device that diverts a proportion of contrast injected by hand through the manifold can potentially reduce volume of contrast delivered to the patient by almost 50% to reduce risk of contrast‐induced nephropathy. Another simple solution to reducing contrast volume is to limit the number of angiographic views and cine runs acquired. A conscious effort by the angiographer to limit the contrast volume to less than the eGFR should be considered.